An Integrated Model of Team Motivation and Worker Skills for a Computer-based Project Management Simulation - Lee, Wee Leong (Institutional Knowledge at Singapore Management University, 2013)
In this paper, I shall propose an integrated model of worker skills and team motivation for a computer-based simulation game that can be used to provide experiential learning to students. They can act as project managers here without being burdened by the costs and risks associated with unsuccessful projects. I shall present an approach of classifying skills into five different types (relevant to IT projects) and apply a five-point competency scale to each skill type. The Pearson Correlation will be applied to the scores of each skill type to generate an efficiency index that will characterize the effectiveness of a team working on a task. I shall also describe a model to represent the relationship between the social needs of team members and their motivation levels. The results of the actual simulation games will be presented here followed by a discussion on the practical implications and recommendations.